Interpersonal Communication and Commitment Organization on Job Motivation: Job Satisfaction as Mediating Variables - Mondra Neldi; Bayu Pratama Azka; Wica Anggreani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2022)
This research was conducted to determine the effect of interpersonal communication and organizational commitment on work motivation and employee job satisfaction as an intervening variable at PT. Karya Sawitindo Mas (KSM) in Muko-muko sub-district. The method used in this study is a quantitative method. This research was conducted with a sample of 106 respondents, namely employees of PT. Karya Sawitindo Mas (KSM) in Muko-muko sub-district. Collecting data in this study using questionnaires, observation, and documentation studies. Analysis of the data used is multiple linear regression analysis with the help of SPSS 21.0 program. Based on the results of the analysis of the research that has been done, the results found that (1)There is no influence between Interpersonal Communication on Employee Job Satisfaction at PT. Karya Sawitindo Mas (KSM), (2)There is no influence between Organizational Commitment on Employee Job Satisfaction at PT. Karya Sawitindo Mas (KSM), (3)There is an influence of interpersonal communication and work motivation on employee job satisfaction at PT. Karya Sawitindo Mas (KSM), (4)There is a unidirectional relationship between interpersonal communication and work motivation, (5)There is a unidirectional relationship between organizational commitment to work motivation, (6)There is a unidirectional relationship between employee job satisfaction and work motivation, (7)There is no influence between interpersonal communication and organizational commitment on work motivation which is associated with employee job satisfaction.